PERAN MODAL PSIKOLOGIS SEBAGAI MEDIATOR PADA HUBUNGAN PERSEPSI DUKUNGAN ORGANISASI TERHADAP KINERJA INDIVIDUAL KARYAWAN - Hilmma Hermawan; Zamralita Zamralita; Rita Markus Idulfilastri (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2022)
This study discusses about individual work performance of employees who have an above average IWP score, experienced organizational change. The purposes of this study was examined the mediating effect of psychological capital in relation of perceived organizational support and individual work performance. A total of 334 employees with a minimum one year experience of work participated in this study. The study was using adapted form of IWPQ-46, POSS-36, and PCQ-24 questionnaires. Measurement being done with Structural Equation Modeling (SEM) method and measurement model using Confirmatory Factor Analysis (CFA) with Lisrel 10.0. Structural model testing showed that perceived organizational support significantly correlated with individual work performance (SFL=+0,13, t-values = +3,43), and significant mediating effect of psychological capital was found. Only support from optimism mediated the perceived organizational support and individual work performance of employees (SFL=+0,76, t-values = +12,16), and neither support from sef-efficacy, hope and resiliency show any significant correlations as mediating variables. As conclusion, hypotheses was tested and confirmed. The findings shows perceived organizational support positively correlated with individual work performance, and support from optimism can help buffer the impact of less perceived organizational support condition on employees’ performance. The other dimensions of psychological capital show no significant correlations.